PELATIHAN DIGITAL MARKETING SEBAGAI PENUNJANG KEWIRAUSAHAAN SISWA SMKN 7 SURABAYA - Andarmadi Jati Abdhi Wasesa; Yunia Dwie Nurcahyanie; Djoko Adi Walujo; Titik Koesdijati (Kanigara, 2022)
The purpose of this community service activity is to broaden students' knowledge about marketing, especially digital marketing. Entrepreneurship as one of the materials in the SMK curriculum has been successfully implemented as an alternative in producing graduates who have had an average career as employees, become entrepreneurs who are able to make a product or service and sell it to the market. However, in practice students only learn how to make and sell, not to market and develop their business. Meanwhile, the world is currently entering the era of e-commerce where the majority of products are marketed via the internet. This service activity is carried out to increase students' insight and skills in order to develop and expand the market for selling their products so that it will increase business turnover. The training is carried out using a workshop method, where students practice marketing their products through Instagram and Facebook. After that, an evaluation of the increase in customer engagement is carried out. From the results of the evaluation, it was found that engagement increased by 20% after being paid to promote students' business social media.